SISTEM INFORMASI PERPUSTAKAAN ONLINE PADA SMP NEGERI SATU ATAP LEREP UNGARAN BARAT (Information Technology and Telematics, 2013)
Abstract : Almost  every  student  of SMP  Negeri  One  Roof  Lerep West Unggaran already have access to the Internet through a computer or laptop. With online internet-connected system is expected  to  provide   convenience  for  students  in  finding information library books, although not in the school..The old system is not computerized inhibit  students in searching the required books. This  research aims to create an online library of information systems at the SMP Negeri Satu  Atap  Lerep  Ungaran  Barat  in  order  to   assist   the students in searching and get a book that is being sought. The research produce online library information  system with menu book search, information display is equipped with a cover of the book, as well as import and export facilities of data. With the menu book search, the students can search the desired book. Data collection  can be done with excel file import facilities at the library information system. By export to excel file to facilitate matching of data at the time of the book, while the export of data to members of the library can be used as a report to the Head of School. Keywords: Information Systems, Library SMP